The Impact of Nutrients on Diabetes - Samer Wissam Younes (Journal of Bioinformatics And Diabetes, 2024)
Over the past 20 years, the number of persons with diabetes has more than doubled globally. The purpose of this review article is to investigate the connection between certain vitamins and diabetes. Diabetes patients have been found to have decreased amounts of certain antioxidant vitamins including A, C, and E, presumably as a result of the requirement to control oxidative stress brought on by problems with glucose metabolism. Retinol-binding protein has regulatory and adipocytokine function. Thiamine, pyridoxine, and biotin levels are also decreased in diabetics. Studies have shown that it restricts the absorption of several nutrients, such as vitamins B9 and B12, thus diabetics must frequently replenish these vitamins. Low vitamin D levels increase the risk of developing diabetes and associated complications, such as cardiovascular disease. Although some studies indicate that vitamin K supplementation can enhance glucose metabolism, it is not known if vitamin K supplementation can prevent or repair oxidative damage. Numerous studies have demonstrated the detrimental consequences of excessive vitamin supplementation. The association between a few nutrients—specifically, vitamins A, D, C, B3, B6, B9, Zn, B12, E, B1/K, and irons—and the already mentioned pathways implicated in diabetes—as well as their potential regulatory activity—will be analyzed in the review that follows.
Keywords: Diabetes